2016
DOI: 10.1186/s40659-016-0081-8
|View full text |Cite
|
Sign up to set email alerts
|

The anti-cancerous activity of recombinant trichosanthin on prostate cancer cell PC3

Abstract: ContextTrichosanthin produced in the root tube of Trichosanthes kirilowii shows anti-tumor activity on a series of cancer cells including Hela, MCF-7, HL-60. But there is little information about its effect on the carcinogenesis of prostate cancer.ObjectiveThis work was designed to study the role of trichosanthin on prostate cancer cells PC3.Materials and methodsTrichosanthin was expressed in BL21 strain and purified by affinity chromatography. MTT assay was designed to determine the effect of trichosanthin on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Miao et al (4) reported that TCS successfully induced apop-4) reported that TCS successfully induced apop-) reported that TCS successfully induced apoptosis in glioma cells in a dose-and time-dependent manner by targeting leucine-rich repeat-containing G-protein coupled receptor 5 and downregulating the Wnt/β-catenin signaling pathway. It has also been reported that recombinant TCS inhibits the proliferation of PC3 cells in a dose-dependent manner in vitro, as well as significantly reducing prostate tumor weight and prostate tumor volume in vivo (2). In the present study, it was demonstrated that TCS potently radiosensitizes Recombinant TCS has been demonstrated to inhibit prostate cancer by activating the caspase-8-regulatory pathway to induce the apoptosis of PC3 cells (2).…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…Miao et al (4) reported that TCS successfully induced apop-4) reported that TCS successfully induced apop-) reported that TCS successfully induced apoptosis in glioma cells in a dose-and time-dependent manner by targeting leucine-rich repeat-containing G-protein coupled receptor 5 and downregulating the Wnt/β-catenin signaling pathway. It has also been reported that recombinant TCS inhibits the proliferation of PC3 cells in a dose-dependent manner in vitro, as well as significantly reducing prostate tumor weight and prostate tumor volume in vivo (2). In the present study, it was demonstrated that TCS potently radiosensitizes Recombinant TCS has been demonstrated to inhibit prostate cancer by activating the caspase-8-regulatory pathway to induce the apoptosis of PC3 cells (2).…”
Section: Discussionsupporting
confidence: 63%
“…Trichosanthin (TCS) is purified from the root tuber of Trichosanthes kirilowii (1). In China, TCS has been used historically as an abortifacient agent in early and midterm pregnancy and to treat invasive moles, ectopic pregnancies and hydatidiform moles (1,2). TCS is a typical type I ribosome-inactivating protein, which attacks eukaryotic cells ribosomes via its rRNA N-glycosidase activities (2).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Novelty, many biologically active ingredients of T. kirilowii were found to play important roles in lipid metabolism, anti‐inflammatory activity, and hypoglycemic activity (Iwabuchi, Kohno‐Murase, & Imamura, ; Shidoji & Ogawa, ). In addition, proteins extracted from T. kirilowii exert antitumor biological function (Li, Li, Zhang, Wang, & Zhang, ; Miao et al, ; Shaw, Lee, & Wong, ; Shi, Wong, & Shaw, ). TKP is a serine protease protein extracted from the fruit of T. kirilowii .…”
Section: Introductionmentioning
confidence: 99%